Morphology and Phylogeny of Five New Ganodermataceae (Polyporales) Species for Vietnam - Nguyen, Trang Thi Thu; Le , Nhung Thi Trang; Nguyen, Tan Khanh; Nguyen, Huynh Van Thi; Nguyen, Hoang Duc; Tran, Linh Thuoc; Van, Kim Thuong Pham; Tran, Manh Hung (Research Aspects in Biological Science Vol. 4, 2022)
Members of the Ganodermataceae are used in traditional medicine in Asian countries. In Vietnamese Traditional Medicine, these mushrooms are used to treat several diseases since the 15th century. In this study, five new Ganodermataceae specimens as Ganoderma multiplicatum, Ganoderma sinense, 2 strains of Ganoderma lingzhi, and Amauroderma subresinosum collecting from Kon Ka Kinh National Park, Vietnam, were classified by morphology and 5.8S-ITS rDNA phylogenetic analysis. Colour photographs of macro-micro features and a phylogenetic tree were provided and discussed. This is the first report of new records of Ganoderma multiplicatum, Ganoderma sinense, two strains of Ganoderma lingzhi, and Amauroderma subresinosum for Vietnam. This research contributed to the distribution of new Vietnamese Ganodermataceae in geography, morphological characteristics, and rDNA sequences.